Breaking down the wall between nature and nurture: An exploration of gendered work preferences in East and West Germany - Luise Görges; Miriam Beblo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We study a possible nurture effect of political systems on the evolution of gender differences in work preferences by exploiting the 41-year division of Germany and its reunification in 1990 as a natural experiment. We investigate whether disparate political and social systems produced different gender gaps in preferences with respect to work and specific job attributes (high income, promotion opportunities) as, e.g., the higher female labour force participation in the former German Democratic Republic (GDR) suggests. Based on the German General Social Survey (ALLBUS) in years 1991, 1998/2000 and 2010/2012, our analyses reveal substantial differences between East and West gender gaps in preferences for work directly after reunification and hardly any convergence over the following 20 years. Regarding job attributes, gender-specific preferences in 1991 do not differ between East and West regions. Until 2010, the gaps vanish in the East but remain stable, or even widen, in the West. Cohort analyses confirm that the effect is driven by respondents who lived their adolescence in separated Germany. Accordingly, our results provide strong evidence for the impact of nurture on preference formation, while age and length of exposure are important determinants of the extent of such impact.
Keywords: C21; J24; P50; 330